PENGARUH PERTUMBUHAN LABA, STRUKTUR MODAL, LIKUIDITAS DAN KOMITE AUDIT TERHADAP KUALITAS LABA - Alfiati Silfi (UIR Press, 2016)
This study aims to examine the effect of earnings growth, capital structure, liquidity and audit committeeon the quality of earnings. Population in this research are manufacturing companies listed in IndonesiaStock Exchange. Companies sampled in this study were more than 26 companies with the observationperiod of the years 2009-2011 in order to obtain observational data as much as 78. Testing and analysisof data using multiple regression with SPSS 16.0. Hypothesis testing results show that the capitalstructure, liquidity and audit committee affects the quality of earnings. While profit growth does not affectthe quality of earnings.